Modeling and Simulation of autonomous mobile robot system for collision avoidance in VR environment using Simscape-Multibody - Nawawi, Sophan Wahyudi; Mohammed Ahmed, Abd Alati Alhadi; Biswas, Hasin Abrar; Jibrin, Mohammed Alih (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Autonomous mobile robots have recently become a centre of attention in the robotics community due to their ease of design, modeling and implementation, making them very lucrative in logistics, monitoring, mapping and other purposes. Fundamentally, collision avoidance is a major aspect of an autonomous mobile robot which requires assistance from other aspects like sensor fusion, localization, path planning etc., to contribute to achieving proper functionality in an open environment, hence the inherently required integration makes it hard to many researchers, robotics and robot enthusiasts to incorporate multi-dimensional functionalities in their system. Sometimes traditional software for robotics makes it harder to acquire actual insight into their system due to a lack of cross-platform compatibility. Therefore, this research aims to demonstrate a way to integrate important aspects required for obstacle avoidance system for design and analysis using a compatible system which is SolidWorks and MatLab simscape multibody, which provides sufficient scope to properly and accurately simulate autonomous systems on a real-time basis that can be used with actual hardware to final implementation. The findings of the study demonstrate that it is very much feasible to use such a method for robotic and other complex mechanics applications, and further analysis of the sensor fusion algorithm reveals some shortcomings of the sensor fusing algorithm and data processing which can be avoided by introducing further sensor sequencing and implementing adaptive neuro fuzzy-based system.